Radio resource allocation in third generation mobile communication systems. - Jorguseski, L. (IEEE Communications magazine)
Code-division multiple access has been widely accepted as the major multiple access scheme in third-generation mobile communication systems. Wide-band CDMA and its hybrid associate time-division CDMA are key elements of the IMT2000 framework of standards. Since the beginning of the 1990s there has been enormous research activity in analysis of the soft (i.e., interference limited) capacity of these CDMA-based systems. Optimal usage of the soft capacity to provide, maintain, and guarantee QoS for different service classes is now becoming a very important issue. Therefore, interest in radio resource allocation has recently. This article presents an overview of RRA schemes (primarily for CDMA-based systems) that are flexible, support traffic services with various QoS requirements, minimize call/session blocking and dropping probabilities, and have acceptable radio resource utilization